Bidirectional Microglia-Neuron Communication in the Healthy Brain - Ukpong B. Eyo; Long-Jun Wu (Neural Plasticity)
Unlike other resident neural cells that are of neuroectodermal origin, microglia are resident neural cells of mesodermal origin. Traditionally recognized for their immune functions during disease, new roles are being attributed to these cells in the development and maintenance of the central nervous system (CNS) including specific communication with neurons. In this review, we highlight some of the recent findings on the bidirectional interaction between neurons and microglia. We discuss these interactions along two lines. First, we review data that suggest that microglial activity is modulated by neuronal signals, focusing on evidence that (i) neurons are capable of regulating microglial activation state and influence basal microglial activities; (ii) classic neurotransmitters affect microglial behavior; (iii) chemotactic signals attract microglia during acute neuronal injury. Next, we discuss some of the recent data on how microglia signal to neurons. Signaling mechanisms include (i) direct physical contact of microglial processes with neuronal elements; (ii) microglial regulation of neuronal synapse and circuit by fractalkine, complement, and DAP12 signaling. In addition, we discuss the use of microglial depletion strategies in studying the role of microglia in neuronal development and synaptic physiology. Deciphering the mechanisms of bidirectional microglial-neuronal communication provides novel insights in understanding microglial function in both the healthy and diseased brain.